Factors Associated with Mental Health and Stress among Healthcare Personnel Responsible for COVID-19 in Lampang Province - Pitspingkum, Watcharaporn; Chautrakarn, Sineenart; Thongprachum, Aksara (Journal of Phrapokklao Nursing College, Chanthaburi, 2025)
This cross-sectional research aimed to explore mental health and stress and to investigate the factors associated with mental health and stress among healthcare personnel. The samples consisted of 384 healthcare personnel responsible for COVID-19 in Lampang Province. The research instruments included a personal factor and performance characteristic questionnaire, the General Health Questionnaire (Thai GHQ–30) with a reliability of .84, and a stress assessment form with a reliability of .93. Data were collected from June to July 2022. Statistics used for data analysis included frequency, percentage, mean, standard deviation, and Chi-square test. The research results revealed that 1) 57.55% of healthcare personnel had no mental health problem and 77.86% of them had stress score at a normal level; 2) the factors that statistically significantly associated with mental health among healthcare personnel were composted of age (p < .01), marital status (p < .001), working age (p < .05), workplace (p < .001), adequacy of income (p < .05), underlying diseases (p < .001), housing characteristics (p < .05), average working hours per day (p < .001), and major roles (p < .001); and 3) the factors that statistically significantly associated with stress among healthcare personnel were composted of age (p < .001), marital status (p < .001), working age (p < .001), current job position (p < .05), workplace (p < .001), monthly income (p < .001), adequacy of income (p < .001), housing characteristics (p < .001), average working hours per day (p < .001), and major roles (p < .01). This research suggests that executives or supervisors should utilize the findings to plan for promoting, preventing, and reducing mental health problems among healthcare personnel responsible for public health emergency situations.